PERANCANGAN DAN PENERAPAN ALGORITMA JAWA UNTUK MENCARI JARAK ANTARA DUA BUAH KOMPUTER DALAM JARINGAN WIRELESS LAN/HOSTPOT - Khairur Razikin; Hero Wintolo; Yuliani Indrianingsih (Institut Teknologi Dirgantara Adisutjipto, 2012)
Wireless networks / hostspot using wave or signal transmission media. Waves or signals emitted from a device called an access point having a particular frequency. Signal beam is formed a circular pattern in which the antenna from the access point to the source signal. In a wireless network signal is captured and used a computer to be able to communicate with each other. PING technique is a method to double check the connection by sending data packets from the sending computer to the destination computer. This process can be seen from the travel time required to transmit data packets. So there is some problems how to convert time obtained from the PING into the distance. Algorithm Jawa can be used to convert units of time-based PING the wireless LAN / hostspot into the distance. Basically, two computers that are in a wireless LAN / hostspot will form a triangular pattern. This pattern will be used algorithm jawa to determine the distance between two computers within the wireless LAN / hostspot by utilizing modifications pythagorean theorem for isosceles triangular pattern and the large angle of 400.